From equation 3 to equation 5

Expand the following: \begin{align} a= \frac{F_b}{m} =&\cssId{Step1}{v(t)=ad}\\[3px] &\cssId{Step2}{v(t)= -\frac{F_b}{m}d}\\[3px] &\cssId{Step3}{v(t)= -\frac{F_b}{m}t+K}\\[3px] &\cssId{Step4}{v(t)= -\frac{F_b}{m}t+v_0}\\[3px] \end{align}

  1. In the first step we calculate the speed equation with the acceleration and variable d
  2. In the second step we take the equation of the acceleration and we change it here
  3. In the third step we take the variable d and we change it for the variable K and the time
  4. In the fourth step we change the variable K for the initial speed